Population pharmacokinetics of tacrolimus in umbilical cord blood transplant patients focusing on the variation in red blood cell counts. (22nd October 2020) - Yoshida, Saki; Fujimoto, Ayumi; Fukushima, Keizo; Ando, Motozumi; Irie, Kei; Hirano, Tatsuya; Miyasaka, Moena; Shimomura, Yoshimitsu; Ishikawa, Takayuki; Ikesue, Hiroaki; Muroi, Nobuyuki; Hashida, Tohru; et al.
Abstract: What is known and objective: The distribution of tacrolimus (TAC), an immunosuppressant used during cord blood transplantation (CBT)—one of the haematopoietic stem cell transplantations, to red blood cell (RBC) is approximately 90% in whole blood. In CBT patients, the total RBC count shows dramatic fluctuation due to conditioning before transplantation, including anticancer agents and total body irradiation, as well as RBC transfusions during the treatment period. Therefore, the amount of TAC in whole blood may show wide variation. However, therapeutic drug monitoring (TDM) of TAC has been performed based on the whole blood concentration. In this study, to contribute to TDM of TAC in CBT, we performed the population pharmacokinetic (PPK) analysis of TAC in 56 CBT patients and investigated the factors that affected the concentration of TAC, focusing the variation of RBC count. Method: A one‐compartment model was applied to the observed whole blood TAC concentrations, and a PPK analysis was conducted with a non‐linear mixed effect model. Results and discussion: Our final PPK model indicated good robustness and accuracy. In addition, haemoglobin (Hb) level was an influential covariate on Vd, which was expressed as Vd(L) = 91.4 × (Hb/8.2) (−1.07) . What is new and conclusion: In this study, our results showed the necessity for the Hb level monitoring during TDM of TAC in CBT patients and provided useful information for improving TDM strategy of TAC. Abstract : Therapeutic drug monitoring of tacrolimus in CBT patients needs to monitor the red blood cell count.